Perkembangan LGBT (Lesbian, Gay, Bisexual, Transgender) sebagai Ancaman Keamanan Global: Studi Kasus Swedia - Adillah, Ghina Nidaul; Rimapradesi, Yulia (Inovasi Saintific Review - Center of Policy Innovation and Social Politics, 2024)
This research discusses LGBT developments that can become a threat to global security with Sweden as a case study. The existence of LGBT communities is considered to be legal in some countries, but there are also countries that violently oppose the existence of these communities. This opposition happens because the existence of LGBT groups is considered to be a new threat in the future and can affect global security. The development of LGBT groups in the world is very influential in various aspects, so therefore this research uses two concepts, such as human security concepts that focus on aspects of personal security and healthy security and the concept of transnationalism movements, while the research method used is an explanatory qualitative method by retrieving data from books, scientific journals, articles and websites. Human security is the protection from various aspects that threaten human existence, including military aspects, global warming, terrorism, malnutrition, disease, and more. Meanwhile, the transnationalism movement is an effort to promote or express rejection of a new change that is happening across countries. The outcome of this study explains that the existence of same-sex sexual activity groups has become a new threat to global security because their existence threatens various aspects of human security such as personal, community, health, and environmental security.